Exploring the Combined Influence of Industrial and Agricultural Waste on Concrete Performance - Shashank Shekhar Kamal; Akshit Lamba (International Journal of Scientific Research in Civil Engineering, 2025)
Concrete remains one of the most widely used construction materials due to its durability, versatility, and cost-effectiveness. However, the rapid increase in the use of Ordinary Portland Cement (OPC), driven by expanding infrastructure and residential development, has raised significant environmental concerns. Cement manufacturing is responsible for nearly 7% of global CO₂ emissions, contributing heavily to climate change. Furthermore, large-scale extraction of natural resources such as limestone and river sand for cement and fine aggregates has resulted in severe environmental degradation. In response, several governments, especially in developing countries, have imposed restrictions on sand mining to mitigate these adverse effects. To address these challenges, researchers are increasingly investigating sustainable alternatives in concrete production. The use of supplementary cementitious materials (SCMs) including fly ash, slag, silica fume, rice husk ash, and metakaolin has shown promising results in enhancing mechanical strength, reducing permeability, and improving hydration properties of blended cement concretes. Despite this, many locally available pozzolanic materials remain underutilized due to insufficient characterization and limited research.